PRODUCING FABRIC MASK AS AN EFFORT OF VIRUS TRANSMISSION PREVENTION AND OPTIMALIZING PEOPLE INCOME DURING COVID19 PANDEMIC (A CASE STUDY IN SUKARATU VILLAGE, CIKEUS SUB-DISTRICT, SERANG BANTEN) - Deni sunaryo (Fakultas Kewirausahaan Universitas Garut, 2020)
Making the mask functioned as a form of prevention in transmission of the virus, because the virus can be transmitted through the mouth, nose and eyes. The idea of ​​making cloth masks stems from the lack of availability of masks and soaring mask prices in the market. Armed with one of the family members who have expertise in the field of sewing then came the idea to produce their own fabric masks with fabric materials that existed at first and then tried to market them at an appropriate price to optimize revenue in the covid-19 pandemic. fabric mask material used is cotton with a variety of funny motives, in addition to the function of health and aesthetic functions to increase people's interest in wearing cloth masks.